Legal Enforcement for IUU Fishing in Indonesian Sovereignty And Jurisdiction: A Case Analysis of The Capture of Foreign Vessels by The Indonesian Government - Ninin ernawati; Maya Shafira; Deni Achmad; Rehulina Tarigan; Ninne Zahara Silviani (Fakultas Hukum Universitas Mataram, 2022)
The cases of IUU Fishing often occurred in Indonesia. This is due to the lack of supervision by the Indonesian government towards foreign vessels that are still fishing in Indonesian territorial and EEZ. IUU fishing caused huge losses to the country. One of the perpetrators of this illegal act was the Thai Silver Sea 2 ship. The ship entered Indonesian territorial waters precisely in Sabang waters, by flying the Indonesian flag to trick the Indonesian government patrolling around Sabang waters. However, gradually the Indonesian government became aware of the existence of foreign vessels which had been suspected by Indonesia for a long time because it often turned off VMS so that its existence could not be detected by the Indonesian government. This study will examine more deeply related to whether the action conducted by Silver Sea 2 Vessels violate Indonesian regulation and UNCLOS 1982? And is the legal enforcement of Illegal Unreported and Unregulated Fishing taken by Indonesian government compatible with UNCLOS 1982?. This research is a normative legal research with a statute approach, and a conceptual approach. Legal material collection techniques are carried out by examining the relevant literature, analyzing various legal references relevant to the problem related to the study to be analyzed further qualitatively and descriptively. The results showed that the actions of SS2 ships violated Indonesian legislation and UNCLOS 1982 and were appropriate when this case was handled by the Sabang district court.